Discourses of Religious Harmony in Q.S. Al-Kāfirūn [109]: An Analysis of Muhammad Sya’roni Ahmadi’s Oral Tafsīr - Ulin Nuha; Mujiburohman (UIN Siber Syekh Nurjati Cirebon, 2026)
Q.S. al-Kāfirūn [109] has frequently served as a Qurʾānic foundation for discussions of interreligious relations. Existing scholarship, however, has focused predominantly on written exegesis, while the production of meaning within oral tafsīr traditions has received comparatively little attention. This study examines the discourse of religious harmony in Muhammad Sya’roni Ahmadi’s oral interpretation of Q.S. al-Kāfirūn [109], with particular attention to the relationship among Qurʾānic interpretation, the plural social context of Kudus, and the social authority of the kiai. This qualitative study is based on an audio-document analysis of transcripts from Sya’roni Ahmadi’s tafsīr lecture at al-Aqṣā Mosque, Menara Kudus. The data are analyzed through Teun A. van Dijk’s Critical Discourse Analysis, encompassing textual analysis, social cognition, and social context. The findings show that Sya’roni Ahmadi constructs a discourse of harmony by distinguishing between ‘religious harmony’ (kerukunan agama), understood as the mixing of doctrines and rituals and therefore rejected, and ‘harmony among religious communities’ (kerukunan umat beragama), understood as peaceful social relations without compromising religious identity and therefore encouraged. This discourse is established through textual legitimation based on Q.S. al-Kāfirūn, historical legitimation through the examples of the Prophet Muhammad and the Wali Songo, and cultural legitimation through Javanese language and locally grounded illustrations. The study demonstrates that oral tafsīr does not merely reproduce Qurʾānic meaning; it also functions as a discursive practice that mediates theological norms and the realities of a plural society through the social authority of a kiai.